Role of Behavioral Addictions in Predicting Reactivity in Bipolar Mood Disorder Patients - Abolghasemi, Abbas (Kowsar, 2014)
BACKGROUND: Behavioral addictions (BAs) can be understood as disorders characterized by repetitive occurrence of reactivity and uncontrolled behaviors. Very few studies have investigated their association with bipolar mood disorders. OBJECTIVES: The present study aimed to determine the role of behavioral addictions in predicting interpersonal behavioral addictions in bipolar mood disorder patients. MATERIALS AND METHODS: This study had a cross-sectional correlation design. The statistical population was composed of all outpatients with bipolar mood disorders referring to clinical centers in Ardabil. The sample included 60 bipolar mood patients selected from patients referring to clinical centers using the available sampling method. A researcher-made behavioral addiction checklist, Interpersonal Behavioral Addictions Index, and exercise, sexual, and work addiction questionnaires, were used for data collection. The data were analyzed with a Pearson’s correlation coefficient and multivariate regression analysis. RESULTS: The results showed a significant negative relationship between behavioral addictions and interpersonal behavioral addictions (P ≥ 0.01). Multivariate regression analysis results also showed that behavioral addictions are significant and can explain 61% of the variance of interpersonal behavioral addictions in bipolar mood patients. CONCLUSIONS: These results suggest that addictive behaviors can affect behavioral addictions in bipolar mood patients. Behavioral addictions lead to negative emotional regulation strategies and result in increased behavioral addictions in these patients. People with high levels of arousal or those who cannot control their behavioral addictions are probably more prone to addictive behaviors.